The imaginaries of a heterogeneous discourse: social representations of Catholicism in the magazines Cabildo, Criterio and Nueva Tierra (1989-2011) (Quinto Sol, 2024)
The objective of this work is, based on the epistemological distinction of the notions of representations and social imaginaries, to explain how the Catholic religious imaginary that coexists since the return of democracy in the Argentine magazines Cabildo, Criterio and Nueva Tierra is verified. For this, a corpus was built consisting of its editorials in the period in which the three were published. At the same time, in the period that extends from 1987 to 2011, the years in which a change of ownership of the Executive Branch in Argentina occurred, although not necessarily through an electoral process: 1989, 1995, 1999, 2001, 2002, 2003, 2007 and 2011. The methodological approach that guides the research is discourse analysis. Two categories of analysis are identified: the social representations of the discursive tradition, on the one hand, and of the Argentine Church, on the other. That is, what magisterial documents they cite and consider legitimate, and what links they establish with the ecclesial institution, respectively.
Keywords: representation; press; Catholicism; discourse